Temporal Resolution and Active Auditory Discrimination Skill in Vocal Musicians - Kumar, Prawin; Sanju, Himanshu Kumar; Nikhil, J. (International Archives of Otorhinolaryngology, 2016)
Introduction Enhanced auditory perception in musicians is likely to result from auditory perceptual learning during several years of training and practice. Many studies have focused on biological processing of auditory stimuli among musicians. However, there is a lack of literature on temporal resolution and active auditory discrimination skills in vocal musicians.Objective The aim of the present study is to assess temporal resolution and active auditory discrimination skill in vocal musicians.Method The study participants included 15 vocal musicians with a minimum professional experience of 5 years of music exposure, within the age range of 20 to 30 years old, as the experimental group, while 15 age-matched non-musicians served as the control group. We used duration discrimination using pure-tones, pulse-train duration discrimination, and gap detection threshold tasks to assess temporal processing skills in both groups. Similarly, we assessed active auditory discrimination skill in both groups using Differential Limen of Frequency (DLF). All tasks were done using MATLab software installed in a personal computer at 40dBSL with maximum likelihood procedure. The collected data were analyzed using SPSS (version 17.0).Result Descriptive statistics showed better threshold for vocal musicians compared with non-musicians for all tasks. Further, independent t-test showed that vocal musicians performed significantly better compared with non-musicians on duration discrimination using pure tone, pulse train duration discrimination, gap detection threshold, and differential limen of frequency.Conclusion The present study showed enhanced temporal resolution ability and better (lower) active discrimination threshold in vocal musicians in comparison to non-musicians.
Keywords: singing; auditory stimulation; temporal auditory area